2012
DOI: 10.1115/1.4007293
|View full text |Cite
|
Sign up to set email alerts
|

Pipe Elbows Under Strong Cyclic Loading

Abstract: Motivated by the response of industrial piping under seismic loading conditions, the present study examines the behavior of steel process piping elbows, subjected to strong cyclic loading conditions. A set of experiments is conducted on elbow specimens subjected to constant amplitude in-plane cyclic bending, resulting into failure in the low-cycle-fatigue range. The experimental results are used to develop a low-cycle-fatigue curve within the strain-based fatigue design framework. The experimental work is supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Fracture of the non-reinforced specimens occurred at the crown area due to excessive cyclic strain in the hoop direction, which is in accordance with previous publications [11], [12]. Upon completion of each test on reinforced elbows, a cutting machine was used to cut the pipe elbows transversely at several locations in order to inspect the cracked area of the steel pipe.…”
Section: Experimental Results For Cyclic Loadingsupporting
confidence: 85%
See 1 more Smart Citation
“…Fracture of the non-reinforced specimens occurred at the crown area due to excessive cyclic strain in the hoop direction, which is in accordance with previous publications [11], [12]. Upon completion of each test on reinforced elbows, a cutting machine was used to cut the pipe elbows transversely at several locations in order to inspect the cracked area of the steel pipe.…”
Section: Experimental Results For Cyclic Loadingsupporting
confidence: 85%
“…Takakashi et al [10] performed in plane-bending low-cycle fatigue tests on pipe elbows specimens with local wall thinning, due to metal loss from erosion corrosion. More recently, the low-cycle fatigue of pipe elbows, subjected to severe cyclic loading, has been investigated experimentally and numerically by Varelis et al [11], [12]. The recent paper by Karamanos [13] offers an overview of pipe elbow mechanical behavior under severe loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…al [14] and demonstrated that ratcheting occurs mainly in the hoop direction, while the ratcheting rate grows proportionally with the increase of the applied cyclic-bending amplitude or the internal pressure. Vishnuvardhan et al [15] and Varelis et al [16] [17] reported additional experimental results concerning the cyclic response of pipe elbows. In these studies, low-cycle fatigue failure was due to the development of through-thickness cracking, followed by a pipe cross-section ovalization at the bend.…”
Section: Introductionmentioning
confidence: 97%
“…In these studies, low-cycle fatigue failure was due to the development of through-thickness cracking, followed by a pipe cross-section ovalization at the bend. In addition, Varelis et al [16] [17] compared the experimental results with design code provisions, highlighting the conservativeness of current design tools in predicting the number of cycles to failure.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was essential to critically evaluate the widely used and recently developed constitutive models against their simulation capability of component responses for determining the state-of-the-art constitutive modeling features and future model development needs. Ratcheting strains of pressurized piping components such as elbow pipe and straight pipe with or without local wall thinning under cyclic loading, have been also studied by experiments and finite element analysis after 2013 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%